Mineral Chemistry and The Stability Temperature of Nickel-Iron Sulfide from Kolaka Ultramafic Rocks, Southeast Sulawesi - Rio Irhan Mais Cendra Jaya; Syahrul Syahrul; Masri Masri (OPHIOLITE: Jurnal Geologi Terapan, 2025)
This study investigates nickel-iron sulfide mineral chemistry and stability from ultramafic rocks in the Kolaka region, Southeast Sulawesi, Indonesia. Sampling was conducted at two Kolaka ultramafic rock outcrop sites in Baula and Wolo sub-districts. The Kolaka Ultramafic Rocks, part of the Kolaka Ophiolite Complex, are primarily composed of lherzolite, harzburgite, olivine websterite, and serpentinites. Sulfide minerals, including pentlandite, pyrite, and chalcopyrite, were observed in these rocks, along with Ni-Fe-rich minerals interpreted as awaruite. Pentlandite, the dominant sulfide mineral, occurs within olivine and chromite replacements, mainly at their rims and serpentine veins. Eight polished sections of ultramafic rocks from both sites were analyzed using EDS SEM to determine the chemical composition of pentlandite. This analysis reveals a variable composition of Ni and Fe, with Ni-rich members more prevalent. Pentlandites from the Baula district have Fe contents of 18.22–27.34 wt%, Ni contents of 32.59–39.10 wt%, and Co contents of 1.24–2.76 wt%, while those from the Wolo district have significantly higher Ni (46.19–53.79 wt%) and Co (2.79–4.18 wt%) contents but lower Fe (8.50–15.18 wt%). Based on the ternary diagram, pentlandites show various formation temperatures (200 to above 600°C). They are separated into two stability groups: Baula’s pentlandite (Ni < 40%, Fe > 18%) with stability temperatures between 200 and 500°C, and Wolo’s Ni-rich pentlandite (Ni > 46%, Fe < 16%) with stability temperatures above 600°C. The formation of Ni-rich pentlandite is attributed to Ni-rich ultramafic rocks reacting with seawater at high temperatures, facilitating efficient Ni scavenging during serpentinization.